2018
DOI: 10.5539/ijef.v10n4p62
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Model for Analyzing the Impact of Strategic Management Accounting Techniques on Quality of Financial Information

Abstract: This paper aims to analyzing the effect of strategic management accounting techniques on quality of financial information in private Jordanian universities in the capital, Amman. The study involves a questionnaire-based survey of dean and heads of department respondents from private Jordanian universities at Amman capital. A total of (212) valid questionnaire was finally obtained for analysis towards achieving the study objectives. Structural equation modeling was performed to understand the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…SEM has the advantage of modelling relationships between multiple variables simultaneously as well as enabling the testing of several hypotheses in a single systematic analysis (Bagozzi & Yi, 2012). More so, the study employs both unobserved (latent) and observed (indicator) variables, and SEM is appropriate as it allows the use of indicators to measure the latent variables as well as enhances the estimation of the statistical significance of constructs and the relationship between variables (Lorraine et al, 2011;Al-Dweikat & Nour, 2018).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…SEM has the advantage of modelling relationships between multiple variables simultaneously as well as enabling the testing of several hypotheses in a single systematic analysis (Bagozzi & Yi, 2012). More so, the study employs both unobserved (latent) and observed (indicator) variables, and SEM is appropriate as it allows the use of indicators to measure the latent variables as well as enhances the estimation of the statistical significance of constructs and the relationship between variables (Lorraine et al, 2011;Al-Dweikat & Nour, 2018).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The measurement scales used for the evaluation of CAS were adopted from the CAS measurement tool developed by Itang (2020a), while the measurement scales for the assessment of FRQ was adopted from van Beest et al (2009). These two tools have been employed in previous studies and indicated to have strong validity and high reliability (see Al-Dweikat & Nour, 2018;Ironkwe & Nwaiwu, 2018;Itang, 2020b;Mbobo & Ekpo, 2016;van Beest et al, 2009). Nevertheless, to boost the researcher's confidence in the research instrument, the composite reliability (CR) test, which helped to ascertain the level of association existing between the constructs and their respective indicators, was performed.…”
Section: Reliability Testmentioning
confidence: 99%